Tweedie Distribution: A Statistical Solution for Unusually Dispersed Data - Zainol Mustafa (Universitas Muhammadiyah Metro, 2025)
The Tweedie distribution has emerged as an effective statistical approach to model data with unusual dispersion characteristics, especially data with mixed discrete and continuous components. In this study, the Tweedie distribution is applied to insurance claims data to model the pattern of claims containing many zero values and large claims that are continuous in nature. With parameter estimation using the iteratively reweighted least squares (IRLS) algorithm in R software, the results show that the Tweedie distribution can handle higher variability (overdispersion) accurately. The estimated power parameter value () of 1.7 indicates that the Tweedie distribution combines the Poisson and Gamma distributions, which are effective in modeling claims data with high dispersion. This study also shows that the Tweedie distribution is able to provide better and more realistic predictions compared to traditional distributions such as Poisson or Gamma, which cannot handle data with mixed characteristics and overdispersion well. These findings provide important contributions to insurance claims modeling and open up the potential for wider applications in various other fields that face data with high variability and mixed patterns.